2008
DOI: 10.1093/ageing/afp009
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of accelerometry with clinical balance tests in older fallers and non-fallers

Abstract: this is the first study of its kind to show a high correlation between accelerometry, the BBS and TUG. Accelerometry could also distinguish between sway responses to differing balancing conditions and between fallers and non-fallers. Accelerometry was shown to be an efficient, quantitative alternative in the measurement of balance in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
90
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 18 publications
10
90
1
9
Order By: Relevance
“…In a study by O'Sullivan et al (34) aimed to determine the correlation between accelerometry and clinical patterns (Berg Balance Scale and the TUG test), to characterize accelerometer responses and acceleration patterns between fallers and non-fallers, the authors report that the Berg Balance Scale, tends to be subjective, while the TUG quantifies a functional impairment of the individual, but it requires a subjective evaluation to balance the assessment. Other alternatives require sophisticated and expensive equipment, therefore, the accelerometer is a potential solution to the problem, reaching the conclusion that it was the first type study which showed a high correlation between the instruments and accelerometry can also distinguish between stabilizing responses to different equilibrium conditions, proving to be an efficient alternative, quantitatively measuring the balance of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by O'Sullivan et al (34) aimed to determine the correlation between accelerometry and clinical patterns (Berg Balance Scale and the TUG test), to characterize accelerometer responses and acceleration patterns between fallers and non-fallers, the authors report that the Berg Balance Scale, tends to be subjective, while the TUG quantifies a functional impairment of the individual, but it requires a subjective evaluation to balance the assessment. Other alternatives require sophisticated and expensive equipment, therefore, the accelerometer is a potential solution to the problem, reaching the conclusion that it was the first type study which showed a high correlation between the instruments and accelerometry can also distinguish between stabilizing responses to different equilibrium conditions, proving to be an efficient alternative, quantitatively measuring the balance of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…No requieren el uso equipo especializado y los resultados son inmediatos. Sin embargo, existe interés por eliminar la subjetividad de estas pruebas [1,3]. También existen pruebas cuantitativas que determinan el riesgo de caída a partir de las características temporales del balanceo.…”
Section: Introductionunclassified
“…Es decir, su CoP estará contenido dentro de unárea menor [4]. Buscando medir el balanceo de los pacientes se han examinado métricas basadas tanto en el CoM como en el CoP tratando de relacionarlo con el riesgo de caída y las evaluaciones BBS y TUG [3,[5][6][7]. Algunas de estas pruebas requieren el uso de plataformas de fuerza de alto costo [5], de acceleróme-tros [3,6] o de cámaras [7,8].…”
Section: Introductionunclassified
See 2 more Smart Citations